Traditionelle Moscheebauten (Bulletin KNOB, 1989)
Architecture stands apart within 'materialized' culture. Until now her socio-historical and ethno-sociological expressiveness - at least for Africa - has been neglected. Between Sahara and tropical rainforest the West-African buildings consist of loam, the oldest and most perishable material on earth. Nowadays this material is disdained and more and more replaced by modern building materials. The traditional methods are threatened by this, before they even had been recognized as venerable cultural heritage of this area. Between 1976 and 1986 the Frobenius-lnstitut Frankfurt has executed a research project to document West- African loam architecture, which project has been financed by the Foundation Volkswagenwerk. Next to native 'old-soudanese' settlements building-forms of the 'young soudanese', North-African Islamic influenced complexes have been examined. A remarkable type of the last category is the Islamic church, the mosque. The mosque is an accomplishment of the community, which presupposes technical knowledge and craftsmanship. Apart from religious motivation the exterior for generations gave rise to preservation in spite of the perishableness of the material. Constructions with plans till 3000 m2 and building-histories more than 600 years old prove their extraordinary meaning. The regional research payed attention to architectural main points in Mali (Niger-lnnerdelta), Burkino Faso and Ivorycoast (Dyula-regions) and in Niger (Haussa-area). Measurement and photographic documentation have been brought up by means of ethnographic and special data. From the 300 catalogued mosques 177 have been represented in designs and detailed drawings (printed); 600 photo's are recorded. Special considerations were applied to the building-process, technological, economical and sociological questions. The development of style during the observed period was interesting, especially because one was able to reconstruct the building process of disappeared mosques of the last 80 to 100 years by means of drawings (Archives: IFAN/Dakar, Musée l'Homme/Paris, Frobenius-Institut/Frankfurt). The representation of 'static', never changing traditional building-methods could be examined. The loam-mosques are an independent West-African creation. Local differences are based on an original adaption-process of Islamic predecessors to the local architecture. Besides 'Africanisements' can be pointed out architecturally in Islamic isolations as well as religious renovation movements from the 19th century until now. Central purpose of the referee was documentation as basis for the understanding of cultural relations. It is to be hoped that her work will inspire to the execution and continuation of independent forms.